ANALISIS INFLUENCER MARKETING PADA PLATFORM MEDIA SOSIAL INSTAGRAM HOTEL ROYAL PALM JAKARTA - Adellia, Tabitha Putri; Abdullah, Taufik (JURNAL MEKAR, 2024)
This study investigates the role of influencer marketing on social media, specifically Instagram, as a strategic marketing approach in the hospitality industry, with a focus on Hotel Royal Palm Jakarta. Recognizing the importance of social media in contemporary travel information access, the research highlights how hotels can leverage influencers to establish and maintain strong customer relationships. The hotel utilizes influencer marketing to promote its affordable "all you can eat" events, demonstrating an effective strategy for increasing brand awareness and attracting customers. The selection criteria for influencers are established, focusing on food vloggers and hotel reviewers, with rigorous evaluation processes supported by the Phlanx software. This study reveals that successful influencer campaigns positively impact guest reservation decisions and meet customer expectations. Data from interviews with fifteen hotel guests indicates a strong correlation between influencer content and guest satisfaction, leading to repeat visits. While the research acknowledges limitations, such as the small sample size and focus on the management team, it offers valuable insights into the effectiveness of influencer marketing in the hospitality sector. The findings contribute to the literature on digital marketing strategies and provide recommendations for future research, including exploring influencer roles on emerging platforms like TikTok and considering different hotel brands to broaden the scope of understanding.